Earthen floors : a modern approach to an ancient practice - Crimmel, Sukita Reay; Thomson, James, 1977- (New Society Publishers, 2014)
Down and dirty? a complete step-by-step guide to making, installing, and living with beautiful, all-natural earthen floors.